Family Visiting Service System for Prisoners in Class II B Tanjung Pura Detention Centre - Bangun P Manalu; Rahul Ardian Fikri (International Journal of Sociology and Law, 2024)
In order to prevent the distribution and use of narcotics in detention centers, narcotics dealers are subject to a specific minimum penalty for the type of punishment that can be imposed on criminals. The social issue in giving to prisoners who have committed criminal acts of narcotics abuse is the prisoner's right to receive a reduced sentence if they have good behavior while undergoing training. The nature of the research used is normative legal research and the data collection method used in this research is secondary data obtained through library research, namely by conducting research on various literature such as books, laws, with the aim of to look for concepts or understandings related to the problem of the Family Visiting Service System for Inmates in the Class II B Tanjung Pura Detention Center. Legal Arrangements for the Family Visiting Service System for Inmates in the Class II B Tanjung Pura Detention Center can be interpreted as a place where people are gathered who violate the rules and norms that exist in society. Meanwhile, the principle adopted by correctional institutions is to position prisoners as subjects who are seen as individuals, ordinary citizens, and as creatures of God. Based on this, in prison prisoners receive guidance and guidance with the hope that after completing their sentence, prisoners can socialize with the community and improve their skills so they can live independently in society. Factors Inhibiting the Family Visiting Service System for Inmates in the Class II B Detention Center in Tanjung Pura, from children to adults, are not free from narcotics, in Indonesian law enforcement the morning criminal sanctions for narcotics dealers do not seem to be feared by the dealers because it is proven by Year after year the problem of narcotics always increases.